Genetic Transformation of Metroxylon sagu (Rottb.) Cultures via Agrobacterium-Mediated and Particle Bombardment - Evra Raunie, Ibrahim; Md. Anowar, Hossain; Hairul, Azman Roslan (Hidawi Publishing Coperation, 2014)
Sago palm (Metroxylon sagu) is a perennial plant native to Southeast Asia and exploited mainly for the starch content in its trunk. Genetic improvement of sago palm is extremely slow when compared to other annual starch crops. Urgent attention is needed to improve the sago palm planting material and can be achieved through nonconventional methods. We have previously developed a tissue culture method for sago palm, which is used to provide the planting materials and to develop a genetic transformation procedure. Here, we report the genetic transformation of sago embryonic callus derived from suspension culture usingAgrobacteriumtumefaciens and gene gun systems.Thetransformed embryoids cellswere selected against Basta (concentration 10 to 30mg/L). Evidence of foreign genes integration and function of the bar and gus genes were verified via gene specific PCR amplification, gus staining, and dot blot analysis.This study showed that the embryogenic callus was the most suitable material for transformation as compared to the fine callus, embryoid stage, and initiated shoots.The gene gun transformation showed higher transformation efficiency than the ones transformed using Agrobacteriumwhen targetswere bombarded once or twice using 280 psi of helium pressure at 6 to 8 cm distance.